If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + 9 = 15x + -4 Reorder the terms: 9 + 16x = 15x + -4 Reorder the terms: 9 + 16x = -4 + 15x Solving 9 + 16x = -4 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 9 + 16x + -15x = -4 + 15x + -15x Combine like terms: 16x + -15x = 1x 9 + 1x = -4 + 15x + -15x Combine like terms: 15x + -15x = 0 9 + 1x = -4 + 0 9 + 1x = -4 Add '-9' to each side of the equation. 9 + -9 + 1x = -4 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = -4 + -9 1x = -4 + -9 Combine like terms: -4 + -9 = -13 1x = -13 Divide each side by '1'. x = -13 Simplifying x = -13
| (X+7)(3x+5)=0 | | 3(4x-3.2)=5x-9.6 | | 3(2-3x)=52 | | 2x-4+3x=7x-3 | | 70x+90=90 | | 7x-5=5x-6 | | x^2-6x=22 | | 6u-9+3(2u+3)=4(u+3) | | 4(x+1.78)=3x | | 8n+16=8 | | 200x-0.08=600x+0.52 | | 3x+7=-2x+27 | | 6-6x=6x-10x+10 | | 3.9x-73=2.4x+5 | | 8z-24=6+2z | | 5m-7=10+3m | | 6.2=8x+1.4 | | 6-6x=6x-10+10 | | 6n-2=1 | | -4(v-4)=-7+37 | | 2y-8+14=-6 | | 2t-7=-16+t | | 3+3u=6 | | -19=5(u-5)-8u | | -3x^3+3x^2-21x+7=0 | | p-24=-19 | | 4+x-6=6x+3x+2 | | 4x-13.2=x | | 2.4x-8.6=10.6 | | -5+2u=-13 | | 17+7=31 | | 3p+7p+22=2 |